Echocardiography in patients with hypertrophic cardiomyopathy: usefulness of old and new techniques in the diagnosis and pathophysiological assessment - Losi, Maria-Angela (BioMed Central, 2010)
Hypertrophic cardiomyopathy (HCM) is one of the most common inherited cardiomyopathy. The identification of patients with HCM is sometimes still a challenge. Moreover, the pathophysiology of the disease is complex because of left ventricular hyper-contractile state, diastolic dysfunction, ischemia and obstruction which can be coexistent in the same patient. In this review, we discuss the current and emerging echocardiographic methodology that can help physicians in the correct diagnostic and pathophysiological assessment of patients with HCM.